Pengaruh Self Regulated Learning dan Digital Literacy Terhadap Hasil Belajar IPA Siswa Kelas VII SMP - Yowelna Tarumasely (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Self-regulated learning and digital literacy are very important because both have implications for student learning outcomes. This study aims to find out (1) whether there is an influence of self-regulated learning on learning outcomes, (2) whether there is an influence of digital literacy on learning outcomes, (3) whether there is an influence between self-regulated learning and digital literacy simultaneously on student learning outcomes. The research subject is a student of class VII of Ambon State Junior High School 9 on IPA subjects. The method used is a quantitative method. The results showed that: 1) there is an influence of self-regulated learning on learning outcomes, 2) there is an influence of digital literacy on student learning outcomes, and 3) there is a simultaneous influence of self-regulated learning and digital literacy on student learning outcomes. In conclusion, student learning outcomes are also influenced by self-regulated learning and digital literacy owned by students